PERBELANJAAN BERMANFAAT DAN TIDAK MEMBAZIR MENGIKUT PERSPEKTIF ISLAM - Hasan, Surtahman Kastin (Jurnal Syariah, 2019)
Spending one's property or income in a manner of extravagance is strictly forbidden in Islam. Over spending in consumption of goods will lose not only one 's potential benefits of the future in term of profit gains, but also will hindrance country 's potential of economics development in term of investment opponunities. One should sacrifice current useless consumption, in turn increase investment courses in order to gain better and sounding life for the whole country in the future.